Teleworking in the post-pandemic period COVID-19 - reasons and aspects of implementation in the Czech Republic - Jaroslav Vrchota; Monika Marikova; Petr Řehoř (Eastern Journal of European Studies, 2025)
While teleworking used to be a desirable benefit, it has now become a normal part of the employment relationship and the only way for some employees to continue doing their jobs. The main objective of this paper is to evaluate the aspects affecting the adoption of teleworking in companies. The paper is based on research conducted after the COVID-19 pandemic (late 2020 to mid-2022) and builds on research conducted during the pandemic in 2019, which investigated factors influencing the length of TW (teleworking) implementation in small and medium-sized enterprises in the Czech Republic. In this paper, the authors evaluated 17 aspects that influenced the adoption of teleworking in 216 firms. Using factor analysis, the authors grouped the aspects of teleworking into 3 factors, which were named as follows: Current labour market needs from the perspective of employees (summarizing 8 aspects), Barriers faced by firms (7 aspects) and COVID specifics (2 aspects).